2018
DOI: 10.1158/0008-5472.can-17-3912
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MST/Hippo Signaling in a Genetically Engineered Mouse Model of Fusion-Positive Rhabdomyosarcoma Accelerates Tumorigenesis

Abstract: A hallmark of fusion-positive alveolar rhabdomyosarcoma (aRMS) is the presence of a chromosomal translocation encoding the fusion oncogene. Primary cell-based modeling experiments have shown that is necessary, but not sufficient for aRMS tumorigenesis, indicating additional molecular alterations are required to initiate and sustain tumor growth. Previously, we showed that -positive aRMS is promoted by dysregulated Hippo pathway signaling, as demonstrated by increased YAP1 expression and decreased MST activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…The inhibition of MST/Hippo signaling in a genetically engineered FPRMS mouse model leads to enhanced invasion and proliferation of FPRMS tumors [102]. Yes-associated protein 1 (YAP1), a downstream effector of the Hippo pathway, has elevated expression levels in FNRMS.…”
Section: Hippo Signaling Pathwaymentioning
confidence: 99%
“…The inhibition of MST/Hippo signaling in a genetically engineered FPRMS mouse model leads to enhanced invasion and proliferation of FPRMS tumors [102]. Yes-associated protein 1 (YAP1), a downstream effector of the Hippo pathway, has elevated expression levels in FNRMS.…”
Section: Hippo Signaling Pathwaymentioning
confidence: 99%
“…Hippo signaling is a fundamental player in tumor biology (21)(22)(23)(24)(25)(26). MST1/2 kinases phosphorylate and activate LATS1/2, which in turn phosphorylate two transcriptional coactivators, Yes-associated protein (YAP) and WW domain-containing transcription regulator 1 (TAZ), contributing to their cytoplasmic sequestration and functional suppression (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…This effect was not observed in DDR repressed COL1 tumours, which indicated that this was an effect specifically mediated by interactions between DDRs and COL1. Loss of MST and/or LATS kinases, by either genomics deletions, epigenetic silencing or posttranslational regulation, is a characteristic of many types of sarcomas 97,99,100,103,106,[144][145][146] , which are also detected in sarcoma-derived cell lines, including in HT1080 cells 99 . Functionally, the MST/LATS kinases are considered to be tumour suppressors, and consistently genetic deletion of these kinases in mice increases tumorigenicity and the development of sarcomas 145,[147][148][149] .…”
Section: Discussionmentioning
confidence: 99%
“…The decoupling between MST/LATS kinases and YAP1 regulation observed here is consistent with evidence showing that deregulation of these kinases does not necessarily alter YAP activity (summarized in 154 ). Indeed, MST/LATS kinases can regulate downstream effector other than YAP/TAZ 104,106,145,154,155 . Conversely, YAP activity is also regulated by LATS-independent mechanisms [156][157][158] .…”
Section: Discussionmentioning
confidence: 99%